2018
DOI: 10.1177/1091581818813601
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept Evaluation of JTPc and Tp-Tec as Proarrhythmia Biomarkers in Preclinical Species: A Retrospective Analysis by an HESI-Sponsored Consortium

Abstract: Introduction: Based on the ICH S7B and E14 guidance documents, QT interval (QTc) is used as the primary in vivo biomarker to assess the risk of drug-induced torsades de pointes (TdP). Clinical and nonclinical data suggest that drugs that prolong the corrected QTc with balanced multiple ion channel inhibition (most importantly the l-type calcium, Cav1.2, and persistent or late inward sodium current, Nav1.5, in addition to human Ether-à-go-go-Related Gene [hERG] IKr or Kv11.1) may have limited proarrhythmic liab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…As previously demonstrated, JTp and Tpe intervals both require HR correction similar to the QT interval. 3 Long RR can lead to overcorrection and short RR can lead to under correction when using the Bazett correction formula. 35,36 The Spence correction formula 17 was shown to efficiently model the QT, JTp, or Tpe interval to HR relationship enabling an individual linear correction similar to the formula created by Holzgrefe et al 37 A high vagal tone or a low sympathetic tone results in a longer QT interval, indicating that both the sympathetic and parasympathetic tones influence the QT interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously demonstrated, JTp and Tpe intervals both require HR correction similar to the QT interval. 3 Long RR can lead to overcorrection and short RR can lead to under correction when using the Bazett correction formula. 35,36 The Spence correction formula 17 was shown to efficiently model the QT, JTp, or Tpe interval to HR relationship enabling an individual linear correction similar to the formula created by Holzgrefe et al 37 A high vagal tone or a low sympathetic tone results in a longer QT interval, indicating that both the sympathetic and parasympathetic tones influence the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies by the Health and Environmental Sciences Institute consortium have indicated that the JTp interval is also a suitable alternative to QTc in canines and nonhuman primates. 2,3 Acute stress, mediated (at least, partially) by blood epinephrine, is a common confounding factor known to affect ECG parameters in all species. In a large proportion of humans, epinephrine has been shown to prolong the QT interval.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similarly, a recent retrospective analysis of data from nonclinical studies in dogs and nonhuman primates suggests a similar discrimination for JTp nonclinically. 40 Despite this apparent concordance, only a small proportion of responders (34%) support the use of JTp as a novel proarrhythmia biomarker in CV SP studies. It should be noted that a comparable proportion (33%) were undecided regarding support for the use of JTp in SP studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ion channel responsible for that change appears to differ in humans vs dogs. This conclusion was reached upon examining the ECG changes associated with the administration of several compounds known to induce ion channel inhibition and ECG changes in humans [6], including dofetilide, sotalol, verapamil, and cisapride.…”
Section: Comparative Toxicitymentioning
confidence: 99%